THE IDEALISM OF TEACHERS AS PROFESSIONAL EDUCATORS IN FACING THE ERA OF GLOBALIZATION 4.0 - Irfan Maulana Sidik; Henny Suharyati; Widanengsih Fujiastuti (International Journal of Teaching and Learning, 2024)
The idealism of teachers as professional educators in the era of globalization 4.0 is the focus of this research. Rapid changes in technology and global connectivity give rise to new challenges in the field of education. This research aims to explore an in-depth understanding of how teacher idealism can form a strong foundation in facing changes in this era. Through a descriptive qualitative research method using a literature review, this research explores educational values relevant to the context of globalization 4.0, identifies required technology skills, and explores teacher involvement in professional development. The results of the discussion show that understanding educational values, developing technological skills, and involvement in professional development activities are the main dimensions of teacher idealism. Teachers who understand these values can create inclusive and adaptive learning environments. Strong technology skills enable teachers to integrate digital tools into teaching, while engagement in professional development ensures they continue to develop in the face of dynamic change. In conclusion, teacher idealism plays a crucial role in shaping education that is relevant, adaptive and responsive to the challenges of the era of globalization 4.0. Efforts to strengthen teacher idealism need to be the main focus in facing the dynamics of the future of education.